Duality of responsibility in international law - Lekkas, S-I (2019)
Duality of responsibility in international law arises when the same conduct entails the international responsibility both of the state and of the individual through which the state acts. The thesis examines the origins of duality of responsibility and what this du-ality entails for the interpretation and application of the rules governing the interna-tional responsibility of states and individuals. In principle, state and individual respon-sibility exist in parallel and are independent from each other. This, however, does not mean that they do not overlap. First, duality of responsibility is the corollary of the du-ality of obligations. This means that the content of certain international obligations of the individual is materially identical to, or necessarily co-determined by, the international obligation of the state. Second, the state can only act through individuals (natural persons). When the same obligation is incumbent on both the state and the individual, both state and individual responsibility may be engaged when the individual’s conduct is attributable to the state. In parallel, the law of individual responsibility has developed its own rules of attribution of conduct. The unprincipled dissociation between the state and the individual acting as its organ or agent for the purposes of engagement of their respective responsibility would amount to a legal, if not logical, contradiction. Third, individual responsibility under international law is predominantly criminal, but not exclusively so. As both states and individuals can be responsible under international law for the same conduct, they must both incur secondary obligations to make reparation for the same injury in whole or in part. In this sense, duality of responsibility also leads to duality of consequences. The thesis argues that duality of responsibility reflects not only a feature, but also the general principle governing the international responsibility of multiple internationally responsible actors: the principle of independent responsibility. More importantly, duality of responsibility occasions, at a substantive level, the gradual merging of the rules and principles of state and individual responsibility into a common law of international responsibility.